BEYOND PAPER POLICY: OPTIMIZING REGIONAL REGULATION ON WASTE MANAGEMENT THROUGH SYSTEMATIC ENFORCEMENT OF ADMINISTRATIVE SANCTIONS - Ernita Rahmadhani Bym; Siti Hudzaifah Miftahul Jannah; Rahmad Hidayat (RADJA PUBLIKA, 2026)
This research aims to formulate a systematic administrative sanction enforcement model to optimize the implementation of Regional Regulation Number 2 of 2018 concerning Waste Management in Kolaka Regency. The background of the problem is based on the high volume of waste which is disproportionate to the effectiveness of law enforcement, creating a significant gap between written policy (das sollen) and reality in the field (das sein). The urgency of this study is crucial given the fact that since the regulation was enacted in 2018, not a single violation has been sanctioned, causing the regulation to lose its deterrent effect and become merely a passive document. This research employs a normative-empirical juridical approach, combining legal document analysis with field data through in-depth interviews with the community and stakeholders. The novelty of the research lies in offering a concrete solution in the form of a tiered and cumulative sanction mechanism design (punitive-reparatoire) that goes beyond previous conventional evaluative studies. The results indicate that the current ineffectiveness of enforcement is caused by the absence of clear Standard Operating Procedures (SOPs), limited human resources, and weak inter-agency coordination. In conclusion, the formalization of a systematic administrative sanction enforcement SOP is absolutely necessary to ensure legal certainty, increase public compliance, and achieve sustainable environmental governance.